2018
DOI: 10.21853/jhd.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Based Co-Design: Tackling common challenges

Abstract: There has been a surge in experience-based co-design (EBCD) efforts for quality improvement in health care and systems design globally. Service users together with staff are playing a far greater role than ever before in the redesign of services and systems of care. EBCD offers a systematic, bottom-up approach to improving service user and staff experiences of care. There is growing interest in the application and potential of EBCD; however, studies indicate common shared challenges, which coalesce around powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 8 publications
4
68
0
Order By: Relevance
“…Coproduction approaches are increasingly seen as a way to address power inequities in collaborating with patients and the public [71]. However, further work is needed to ensure that imbalances of power between healthcare staff, patients, public and organisations as well as issues of equality and diversity are addressed within these collaborative approaches [26,72]. The testing of approaches that can involve a more diverse representation of patients, the public and healthcare staff in line with the protected characteristics in the Equality Act 2010 [73] (e.g.…”
Section: Implications For Developing Patient Experiencementioning
confidence: 99%
“…Coproduction approaches are increasingly seen as a way to address power inequities in collaborating with patients and the public [71]. However, further work is needed to ensure that imbalances of power between healthcare staff, patients, public and organisations as well as issues of equality and diversity are addressed within these collaborative approaches [26,72]. The testing of approaches that can involve a more diverse representation of patients, the public and healthcare staff in line with the protected characteristics in the Equality Act 2010 [73] (e.g.…”
Section: Implications For Developing Patient Experiencementioning
confidence: 99%
“…In any case, the combination of diverse cognitive approaches and different knowledge sets promotes new ideas or the adoption of old ones in new contexts . Co‐design challenges include overcoming power imbalances and variations in commitment, allocating sufficient time and resources to co‐design, clarifying what is actually negotiable and the nature and timing of service user demands …”
Section: Introductionmentioning
confidence: 99%
“…Obtaining relevant and useful input from groups who have no design experience is problematic [7,16,18]. Design professionals are concerned that users are lacking in design conceptual knowledge and experience [10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has identified a number of limitations when using the EBCD and POE strategies to elicit user input. A consistent observation relates to the difficulty users experience when asked to comment on an issue (building design) where they have limited conceptual knowledge or experience [8,10,16]. Jellema, Annemans and Heylighen (2019) suggests that, when examining the role of architecture, most individuals would have difficulty describing how they experience a 'space'.…”
Section: Introductionmentioning
confidence: 99%